A Study On Iranian Students’ Negotiation Of Identity And Intercultural Challenges In Malaysia - Sousefi, Ebrahim Jamali (2019)
The purpose of this research is to examine the identity challenges as well as intercultural adaptation of Iranian students in Malaysia. The objectives are as follows: to examine the ways in which Iranian students define themselves as well as others, to investigate the challenges of religious and cultural identity in Malaysia, to analyze the changing identity of Iranian students in Malaysia, to investigate the types of Iranian students' identity challenges in Malaysia and to formulate typologies of the Iranian students’ identity. This research utilizes a purposive sampling technique. Thirty-six (36) students were chosen as informants for the study. The findings portray overall identity flexibility with some exceptions, among the informants that have helped them to negotiate, construct, and reconstruct meaningful sense of self through their social and cultural interactions. From the informants, these emerging themes centered on meaningful sense of identity, the value of nationality and ethnic heritage, and intercultural differences. A key contribution to the identity discourse is the discovery of four typologies of Iranian students’ identity: Persian-centric identity, Islamic-centric identity, Reformist identity and minority-ethnic identity. The consequences of the influences of the two societies have placed the students in such a condition that they experience a sense of identity security, respect and support. As a result, these students adapt themselves to the host society by changing new identity to adjustment and achieving a kind of identity stability. The main challenges that emerged from the analysis are mainly cultural, religious and economic.